Oligomeric Aromatic Oxides (OAO) Production From Sugarcane Bagasse Lignin by Acid-Catalyzed Solvothermal Liquefaction in Methanol - Cheng, Yi; Yang, Shujuan; Ji, Li; Shi, Hai (Frontiers in Energy Research, 2020)
Extracted alkali lignin (AL) and organosolv lignin (OL) from sugarcane bagasse were acid-catalyzed liquefied in methanol with the aim of producing oligomeric aromatic oxides. Acids were screened for their effects on the output of oligomeric aromatic oxides from alkali lignin liquefaction. Based on the highest amount of lignin conversion, the order of catalytic efficiency was: p-toluenesulfonic acid (TsOH) > CCl3COOH (TCA) > KHSO4 > AlCl3 > H3O40PW12 > H2SO4. The most alkali lignin conversion was 86.2 wt% when catalyzed by p-toluenesulfonic acid. Optimized liquefaction temperatures indicated that AL liquefaction optimum temperature was 250°C and OL was 175°C. GPC characterized AL, OL and resultant products implied that TsOH could degrade both lignins to about 780 g/mol of molecular weight. HSQC-NMR and GC-MS observations suggested that simultaneous vinyl ether cleavage and intermediate stabilization of phenolic hydroxyl group etherification at high temperatures achieved AL liquefaction. Acidolysis of β-ether linkages at mild temperatures was the mechanism of OL liquefaction.